Waterproof PC / PET filling material and preparation method thereof
By introducing modified montmorillonite into PC/PET alloys and adopting specific preparation methods, the problems of degradation and hydrolysis of the alloy during processing are solved, and the stability and water resistance of the material are improved, and are suitable for new energy vehicles and other fields.
Patent Information
- Application Number
- CN202510002897.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-27
Smart Images

Figure BDA0005225942000000031 
Figure HDA0005288569040000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of modified plastics, and in particular relates to a water-resistant PC / PET filling material and a preparation method thereof. Background Art
[0002] PC / PET alloys prepared by blending polycarbonate (PC) and polyethylene terephthalate (PET) have been widely used in many fields such as automobiles, electronic appliances, etc. due to their excellent performance.
[0003] With the rapid development of new energy intelligent driving, a large number of car companies adopting laser radar solutions all need to use low-dimensional change and weather-resistant alloy solutions. Usually, PC / PET alloys with low dimensional change need to add fillers to achieve it. However, due to the characteristics of polyester materials, they show low melt strength and melt viscoelasticity during processing, resulting in system degradation. Its special molecular structure also makes the material extremely easy to hydrolyze, and it will face performance failure when used under harsh outdoor conditions. These characteristics also greatly limit the application of its materials in many fields.
[0004] In the polyester processing, introducing chain extender modification is one of the means to improve the material processability and mechanical properties. Although the addition of commonly used chain extenders can improve this problem, it cannot also take into account the problem of poor water resistance.
[0005] In summary, there is an urgent need for a modifier for PC / PET filling materials to solve the problems of degradation and decreased mechanical properties caused by the introduction of fillers into the system, while also taking into account the problem of poor water resistance. Summary of the invention
[0006] In view of the above problems, the present invention provides a water-resistant PC / PET filling material and a preparation method thereof. The filling material of the present invention has excellent performance and good stability.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A polycarbonate (PC) / polyethylene terephthalate (PET) material, comprising the following raw materials in parts by weight:
[0009] 25-75 parts by weight of PC;
[0010] 15-65 parts by weight of PET;
[0011] 5-30 parts by weight of modified montmorillonite;
[0012] 0-5 parts by weight of processing aids.
[0013] Preferably, the material comprises the following raw materials in parts by weight:
[0014] 45-75 parts by weight of PC;
[0015] 15-45 parts by weight of PET;
[0016] 5-20 parts by weight of modified montmorillonite;
[0017] 0-5 parts by weight of processing aids.
[0018] In one embodiment of the present invention, the PC has a melt flow index of 300°C, 1.2 kg of 3-65 g / 10 min, preferably 7-50 g / 10 min, more preferably 15-35 g / 10 min.
[0019] In one embodiment of the present invention, the intrinsic viscosity of the PET is 0.58-0.87 dl / g, and the intrinsic viscosity is measured using a capillary method.
[0020] In one embodiment of the present invention, the modified montmorillonite is montmorillonite modified with phenylphosphinic acid-modified glycidyl ether.
[0021] In one embodiment of the present invention, the modified montmorillonite is prepared by a method comprising the following steps:
[0022] S1: phenylphosphinic acid is neutralized with an amine compound to obtain phenylphosphinic acid salt;
[0023] S2: Eugenol reacts with epichlorohydrin to obtain eugenol glycidyl ether;
[0024] S3: reacting eugenol glycidyl ether with phenylphosphinate to obtain phenylphosphinate-modified glycidyl ether;
[0025] S4: mixing phenylphosphinic acid modified glycidyl ether with montmorillonite to obtain modified montmorillonite.
[0026] In one embodiment of the present invention, the amine compound in S1 comprises a C3-C18 alkyl tertiary amine, preferably one or more of trimethylamine, triethylamine, tripropylamine, and tributylamine.
[0027] In one embodiment of the present invention, the mass ratio of phenylphosphinic acid to amine compound in S1 is 40-50:30-60.
[0028] In one embodiment of the present invention, the temperature in S1 is 50-70°C and the time is 4-6 hours.
[0029] In one embodiment of the present invention, the mass ratio of eugenol to epichlorohydrin in S2 is 20-40:60-80.
[0030] In one embodiment of the present invention, the temperature in S2 is 40-90° C. and the time is 6-12 hours.
[0031] In one embodiment of the present invention, the reaction in S3 is carried out in a solution; preferably, the solvent is an ester organic solvent, preferably ethyl acetate.
[0032] In one embodiment of the present invention, the temperature in S3 is 20-50° C. and the time is 1-4 hours.
[0033] In one embodiment of the present invention, the mass of montmorillonite in S4 is 1.5-2 times that of the glycidyl ether modified with phenylphosphinic acid.
[0034] In one embodiment of the present invention, S4 is mixed in water; preferably, the water content in the mixture is ≤50 wt%, preferably 10-50 wt%.
[0035] In one embodiment of the present invention, the temperature in S4 is 40°C-100°C and the time is 5-8 hours.
[0036] The preparation reaction involved in the present invention is shown as follows:
[0037]
[0038] In the present invention, processing aids such as: self-antioxidant, lubricant, ultraviolet absorber, flame retardant, toughening agent, compatibilizer, light stabilizer, heat stabilizer, metal deactivator, plasticizer, anti-adhesive agent, colorant, coupling agent, nucleating agent, foaming agent, antibacterial agent, mildew inhibitor, acid scavenger, hydrolysis resistant agent, chain extender, flow modifier, ester exchange inhibitor, matting agent, antistatic agent, reinforcing agent, filler, antifogging agent, light diffuser, infrared absorber, fluorescent brightener and laser marking agent can be used; preferably, the antioxidant is hindered phenol, phosphite , thioesters, benzofurans, acryl-modified phenols, hydroxylamine antioxidants, one or a combination of two or more thereof; preferably, the lubricant is a fatty alcohol, metal soaps, fatty acids, fatty acid esters, montanic acid and its derivatives, amide waxes, saturated hydrocarbons, polyolefin waxes and its derivatives, silicones and silicone powders, and organic fluorines, one or a combination of two or more thereof; preferably, the ultraviolet absorber is a benzophenone, benzotriazole, triazine, benzoate, cyanoacrylate, phenylimidazole, one or a combination of two or more thereof. The above-mentioned additives are all commonly used additives in the field, and their selection and dosage are well known to those skilled in the art.
[0039] Another object of the present invention is to provide a method for preparing a polycarbonate (PC) / polyethylene terephthalate (PET) material.
[0040] A method for preparing the above-mentioned polycarbonate (PC) / polyethylene terephthalate (PET) material, the preparation method comprising the following steps:
[0041] SS1: melt-extrude and granulate PET, modified montmorillonite and optional processing aids to obtain PET masterbatch;
[0042] SS2: After mixing PC and PET masterbatch, extrude and granulate them through a twin-screw extruder to obtain the target material;
[0043] In one embodiment of the present invention, the temperature in SS1 is 200-300°C, and the screw speed is 200-800 rpm.
[0044] In one embodiment of the present invention, the temperature in SS2 is 200-300°C, and the screw speed is 200-800 rpm.
[0045] Another object of the present invention is to provide a use of polycarbonate (PC) / polyethylene terephthalate (PET) material.
[0046] A use of a polycarbonate (PC) / polyethylene terephthalate (PET) material, wherein the material is the above-mentioned material, or is a material prepared by the above-mentioned preparation method, and the material is used as a water-resistant polycarbonate (PC) / polyethylene terephthalate (PET) material, preferably used in the field of new energy vehicles.
[0047] Another object of the present invention is to provide a montmorillonite modified by phenylphosphinic acid modified glycidyl ether
[0048] A montmorillonite modified by phenylphosphinic acid-modified glycidyl ether, wherein the montmorillonite is the montmorillonite used in the above material, or is the montmorillonite used in the above preparation method.
[0049] Another object of the present invention is to provide a method for preparing montmorillonite modified by phenylphosphinic acid-modified glycidyl ether.
[0050] A method for preparing montmorillonite modified by phenylphosphinic acid-modified glycidyl ether, wherein the montmorillonite is the montmorillonite used in the above material, or the montmorillonite used in the above preparation method, and the modified montmorillonite is prepared by a method comprising the following steps:
[0051] S1: phenylphosphinic acid is neutralized with an amine compound to obtain phenylphosphinic acid salt;
[0052] S2: Eugenol reacts with epichlorohydrin to obtain eugenol glycidyl ether;
[0053] S3: reacting eugenol glycidyl ether with phenylphosphinate to obtain phenylphosphinate-modified glycidyl ether;
[0054] S4: mixing phenylphosphinic acid modified glycidyl ether with montmorillonite to obtain modified montmorillonite.
[0055] The positive effects of the present invention are:
[0056] The PC / PET material of the present invention has stable formability and good performance stability and dimensional stability. The material finally obtained can maintain an impact of 43KJ / m after 14 days of double 85 wet heat aging test. 2 , and the flame retardancy remains V0. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is the infrared spectrum of phenylphosphinic acid modified glycidyl ether (PPO-EP-EU-1). DETAILED DESCRIPTION
[0058] In order to better explain the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are only used as illustrations of the present invention and do not limit the description of the present invention.
[0059] The ingredients of the comparative examples and embodiments are as follows:
[0060] Polycarbonate resin: 2150, melt flow index 15g / 10min (300℃, 1.2kg), Wanhua Chemical Group Co., Ltd.
[0061] Polycarbonate resin: 2220, melt flow index 20g / 10min (300℃, 1.2kg), Wanhua Chemical Group Co., Ltd.
[0062] Polyethylene terephthalate resin: CZ-328A, Sanfangxiang Company, with an intrinsic viscosity of 0.87 dl / g;
[0063] Polyethylene terephthalate resin: CZ-5033, Sanfangxiang Company, with an intrinsic viscosity of 0.65 dl / g;
[0064] Phenylphosphinic acid (PPO): Adamas Reagents Ltd.
[0065] Triethylamine: TEA, Jinan Quansheng Chemical Co., Ltd.
[0066] Eugenol (EU): Sinopharm Chemical Reagent Co., Ltd.
[0067] Epichlorohydrin (EP): Sinopharm Chemical Reagent Co., Ltd.
[0068] Sodium hydroxide: Sinopharm Chemical Reagent Co., Ltd.
[0069] Tetrabutylammonium bromide (TBAB): Adamas Reagents Ltd.
[0070] Ethyl acetate: Sinopharm Chemical Reagent Co., Ltd.
[0071] Deionized water: Wanhua Chemical Group Co., Ltd.
[0072] Montmorillonite (MMT): Sodium montmorillonite, Nanocor, USA.
[0073] Antioxidant: Irganox 168, produced by BASF.
[0074] Diphenyl sulfone sulfonate: KSS, conventional flame retardant, Sinopharm Chemical Reagent Co., Ltd.
[0075] Lubricant: PETS, pentaerythritol stearate, Lonza, USA.
[0076] Ester exchange inhibitor: PGP, Quansheng Company.
[0077] Phenylphosphinic acid modified glycidyl ether (PPO-EP-EU-1):
[0078] (1) 28 parts by mass (0.2 mol) of phenylphosphinic acid and 20 parts by mass (0.2 mol) of triethylamine were placed in a beaker and stirred at 50° C. to allow the substances to react fully. The reaction was continued for 6 h, and phenylphosphinic acid salt was obtained after filtering.
[0079] (2) 33 parts by mass (0.2 mol) of eugenol, 93 parts by mass (1 mol) of epichlorohydrin and 1 part by mass of TBAB were added to a three-necked flask equipped with a condenser and a thermometer, reacted at 85°C for 9 hours, cooled to 40°C, 16 parts by mass of a 40 wt% NaOH solution was added dropwise and 0.4 parts by mass of TBAB was added, the reaction was continued for 2 hours, the precipitated NaCl was removed by suction, the water was removed after washing, and eugenol glycidyl ether (EP-EU) was obtained after rotary evaporation and recrystallization.
[0080] (3) 49 parts by mass (0.2 mol) of phenylphosphinate and 44 parts by mass (0.2 mol) of eugenol glycidyl ether were added to a three-necked flask equipped with a condenser and a thermometer, and 32 parts by mass of ethyl acetate were poured in. The mixture was stirred continuously at 23° C. to allow the substance to fully dissolve. The reaction was continued for 4 h. The ethyl acetate was removed by rotary evaporation, and the mixture was placed in a vacuum oven at 100° C. and dried for 5 h to obtain PPO-EP-EU.
[0081] See attached for representation Figure 1 .
[0082] Phenylphosphinic acid modified glycidyl ether (PPO-EP-EU-2):
[0083] (1) 28 parts by mass (0.2 mol) of phenylphosphinic acid and 30 parts by mass (0.3 mol) of triethylamine were placed in a beaker and stirred at 60° C. to allow the substances to react fully. The reaction was continued for 4 h and phenylphosphinic acid was obtained after filtering.
[0084] (2) 33 parts by mass (0.2 mol) of eugenol, 112 parts by mass (1.2 mol) of epichlorohydrin, and 1 part by mass of TBAB were added to a three-necked flask equipped with a condenser and a thermometer, reacted at 80° C. for 8 h, cooled to 50° C., 16 parts by mass of a 40 wt% NaOH solution was added dropwise, and 0.4 parts by mass of TBAB was added. The reaction was continued for 4 h, and the precipitated NaCl was removed by suction, washed with water, and water was removed. After rotary evaporation and recrystallization, eugenol glycidyl ether (EP-EU) was obtained.
[0085] (3) 49 parts by mass (0.2 mol) of phenylphosphinate and 66 parts by mass (0.3 mol) of eugenol glycidyl ether were added to a three-necked flask equipped with a condenser and a thermometer, and 40 parts by mass of ethyl acetate was poured in. The mixture was stirred continuously at 40°C to allow the substance to be fully dissolved. The reaction was continued for 2 h, and the ethyl acetate was removed by rotary evaporation. The mixture was placed in a vacuum oven at 100°C and dried for 5 h to obtain PPO-EP-EU-2.
[0086] Modified montmorillonite (PEE-MMT-1):
[0087] Weigh 30 parts by mass of PPO-EP-EU-1, then add 50 parts by mass of montmorillonite and 30 parts by mass of deionized water, stir at 80°C for 6 hours at a stirring speed of 1500 rpm / min to obtain an aqueous solution of modified montmorillonite. Mass unit: kg.
[0088] Modified montmorillonite (PEE-MMT-2):
[0089] Weigh 30 parts by mass of PPO-EP-EU-1, then add 60 parts by mass of montmorillonite and 40 parts by mass of deionized water, stir at 50°C for 8 hours at a stirring speed of 1500 rpm / min to obtain an aqueous solution of modified montmorillonite. Mass unit: kg.
[0090] The performance test is as follows:
[0091] The impact strength is tested according to ISO 179 standard, with specimen size: 80*10*4mm and notch depth 2.0mm.
[0092] The flexural strength was tested according to ISO 178, with a specimen size of 80*10*4mm and a rate of 2mm / min.
[0093] The Vicat softening temperature (VST) was tested according to ISO 306 standard with a load of 50N and a heating rate of 120℃ / h.
[0094] The combustion grade is tested according to UL-94, the specimen size is 130mm*13mm*1.5mm, and it burns vertically.
[0095] The coefficient of linear thermal expansion (CLTE) is in accordance with ISO 11359, the specimen size is 8mm*10mm*3mm, and the test temperature is -45℃~100℃.
[0096] The infrared spectrum test uses a Fourier transform infrared spectrometer, model WQF-600N, and the test wavelength is 4000~400cm in total reflection mode. -1 .
[0097] Examples 1-3
[0098] The material preparation process is as follows:
[0099] Example 1-2, Process A:
[0100] (1) Preparation of PET masterbatch: PET, modified montmorillonite and additives were placed in a high-speed mixer for mixing according to the mass ratio in Table 1, and the mixture was added to a loss-in-weight feed scale above the feed port of the screw extruder. The temperatures of zones 1-10 of the twin-screw extruder were controlled to be 200° C., 220° C., 240° C., 250° C., 250° C., 250° C., 250° C., 240° C., and 235° C., respectively, and the head temperature was 230° C. The screw speed was controlled to be 700 rpm. The mixture was subjected to the steps of blending, strand drawing, water cooling, air drying, and pelletizing to obtain PET masterbatch.
[0101] (2) Blending and extrusion granulation: PC and PET masterbatches were placed in a high-speed mixer according to the types and amounts of raw materials in Table 1 for mixing and stirring. The mixture was added to a loss-in-weight feeder above the feeding port of the screw extruder. The temperatures of zones 1-10 of the twin-screw extruder were controlled to be 200° C., 220° C., 240° C., 250° C., 250° C., 250° C., 250° C., 240° C., and 235° C., respectively, and the head temperature was 230° C. The screw speed was controlled to be 700 rpm. The mixture was subjected to the steps of blending, stranding, water cooling, air drying, pelletizing, and drying to obtain a PC / PET composite.
[0102] Example 3, Process B:
[0103] (1) Preparation of PET masterbatch: PET, modified montmorillonite and additives were placed in a high-speed mixer for mixing according to the mass ratio in Table 1, and the mixture was added to a loss-in-weight feed scale above the feed port of the screw extruder. The temperatures of zones 1-10 of the twin-screw extruder were controlled to be 230° C., 250° C., 270° C., 280° C., 280° C., 280° C., 280° C., 270° C., and 265° C., respectively, and the head temperature was 260° C. The screw speed was controlled to be 200 rpm. The mixture was subjected to the steps of blending, strand drawing, water cooling, air drying, and pelletizing to obtain PET masterbatch.
[0104] (2) Blending and extrusion granulation: PC and PET masterbatches were placed in a high-speed mixer according to the types and amounts of raw materials in Table 1 for mixing and stirring. The mixture was added to a loss-in-weight feeder above the feeding port of the screw extruder. The temperatures of zones 1-10 of the twin-screw extruder were controlled to be 230° C., 250° C., 270° C., 280° C., 280° C., 280° C., 280° C., 270° C., and 275° C., respectively, and the head temperature was 260° C. The screw speed was controlled to be 200 rpm. The mixture was subjected to the steps of blending, stranding, water cooling, air drying, pelletizing, and drying to obtain a PC / PET composite.
[0105] Comparative Examples 1-6
[0106] The material preparation process is as follows:
[0107] (1) Blending extrusion granulation: polycarbonate resin, PET, PPO, EP-EU, PPO-EP-EU, MMT, PPE-MMT and PGP were put into a high-speed mixer according to the types and amounts of raw materials in Table 1 for mixing and stirring. The mixture was added to a loss-in-weight feeder above the feeding port of the screw extruder. The temperatures of zones 1-10 of the twin-screw extruder were controlled to be 200° C., 220° C., 240° C., 250° C., 250° C., 250° C., 250° C., 240° C., 235° C., respectively, and the head temperature was 230° C. The screw speed was controlled to be 400 rpm. The mixture was subjected to the steps of blending, stranding, water cooling, air drying, pelletizing and drying to obtain a PC / PET composite.
[0108] Comparative Examples 1-4 are compared with Example 2 respectively. Comparative Example 1 is different in that it only contains phenylphosphinic acid modified glycidyl ether, and the others are the same; Comparative Example 2 is different in that it only contains montmorillonite, and the others are the same; Comparative Example 3 is different in that it contains phenylphosphinic acid modified glycidyl ether and montmorillonite, but only physically blended and added, without intercalation modification, and the others are the same; Comparative Example 4 is different in that it does not contain phenylphosphinic acid modified glycidyl ether, and uses common flame retardant KSS and montmorillonite instead, but only physically blended and added, and the others are the same.
[0109] Table 1 Formulas of Examples 1-3 and Comparative Examples 1-4 (Unit: Kg)
[0110] Amount / weight Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 2150 44 29 10.3 29 29 29 29 2220 30 20 34.7 20 20 20 20 CZ-328A 10 20 20 20 20 20 20 CZ-5033 8 10 24 10 10 10 10 168 0.3 0.3 0.3 0.3 0.3 0.3 0.3 PETS 0.4 0.4 0.4 0.4 0.4 0.4 0.4 PGP 0.3 0.3 0.3 0.3 0.3 0.3 0.3 KSS / / / / / / 10 PPO-EP-EU / / / 20 / 10 / MMT / / / / 20 10 10 PEE-MMT-1 7 20 / / / / / PEE-MMT-2 / / 10 / / / /
[0111] Table 2 Performance comparison of Examples 1-3 and Comparative Examples 1-4
[0112] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Flexural modulus / MPa 2800 3500 2900 2400 3300 3200 2900 VST / ℃ 104 111 106 100 109 108 106 CLTE (23~55℃) <![CDATA[60*10 -6 ]]> <![CDATA[45*10 -6 ]]> <![CDATA[55*10 -6 ]]> <![CDATA[80*10 -6 ]]> <![CDATA[50*10 -6 ]]> <![CDATA[55*10 -6 ]]> <![CDATA[60*10 -6 ]]>
[0113] Table 3. Comparison of water resistance of Examples 1-3 and Comparative Examples 1-4
[0114] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Burn Level - 0day V2 V0 V1 V1 NG V1 V1 Burning Level - 7day V2 V0 V1 NG NG V2 V2 Burning Level - 14day NG V0 V1 NG NG NG NG Impact strength / KJ / m2-0day 40 55 50 38 20 35 22 Impact strength / KJ / m2-7day 24 45 30 20 15 19 14 Impact strength / KJ / m2-14day 13 43 22 10 10 11 9
[0115] Note: Double 85 wet heat aging 0day, 7day and 14day, combustion level V0>V1>V2>NG.
[0116] By comparing the physical properties of Examples 1-3 and Comparative Examples 1-4, it can be found that compared with the PC / PET alloy prepared by simply physically mixing the raw materials, the alloy material with direct addition of PPE-MMT has more obvious advantages in VST and impact, and with the increase of content, the toughness and rigidity of the material can be improved simultaneously. By comparing the CLTE of Examples 1-3 and Comparative Examples 1-4, it can be seen that the intercalated modified montmorillonite can further improve the dimensional stability of the material. By comparing the combustion level and impact performance of the double 85 after Examples 1-3 and Comparative Examples 1-4, it can be seen that the alloy performance loss of each component and the unmodified montmorillonite added separately is extremely fast, and the addition of the intercalated modified montmorillonite significantly improves the moisture and heat resistance of the material. By comparing the data of Comparative Example 3 and Example 2, it can be further seen that the process treatment of modified montmorillonite and PET pre-extrusion can enable the modified montmorillonite to play a better effect in the system.
[0117] Those skilled in the art should understand that the present invention is not limited to the above-mentioned embodiments, and that various changes and improvements may be made to the present invention without departing from the spirit and scope of the present invention, and that these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A polycarbonate (PC) / polyethylene terephthalate (PET) material, characterized in that: The material comprises the following raw materials in parts by weight: 25-75 parts by weight of PC; 15-65 parts by weight of PET; 5-30 parts by weight of modified montmorillonite; 0-5 parts by weight of processing aids. Preferably, the material comprises the following raw materials in parts by weight: 45-75 parts by weight of PC; 15-45 parts by weight of PET; 5-20 parts by weight of modified montmorillonite; 0-5 parts by weight of processing aids.
2. The material according to claim 1, characterized in that The PC has a melt flow index of 300°C, 1.2kg of 3-65g / 10min, preferably 7-50g / 10min, more preferably 15-35g / 10min; And / or, the intrinsic viscosity of the PET is 0.58-0.87 dl / g; And / or, the modified montmorillonite is montmorillonite modified by phenylphosphinic acid-modified glycidyl ether.
3. The material according to claim 1 or 2, characterized in that The modified montmorillonite is prepared by a method comprising the following steps: S1: phenylphosphinic acid is neutralized with an amine compound to obtain phenylphosphinic acid salt; S2: Eugenol reacts with epichlorohydrin to obtain eugenol glycidyl ether; S3: reacting eugenol glycidyl ether with phenylphosphinate to obtain phenylphosphinate-modified glycidyl ether; S4: mixing phenylphosphinic acid modified glycidyl ether with montmorillonite to obtain modified montmorillonite.
4. The material according to claim 3, characterized in that The amine compound in S1 comprises a C3-C18 alkyl tertiary amine, preferably one or more of trimethylamine, triethylamine, tripropylamine, and tributylamine; and / or, the mass ratio of phenylphosphinic acid to amine compound in S1 is 40-50:30-60; And / or, the temperature in S1 is 50-70° C., and the time is 4-6 hours.
5. The material according to claim 3, characterized in that The mass ratio of eugenol to epichlorohydrin in S2 is 20-40:60-80; And / or, the temperature in S2 is 40-90° C., and the time is 6-12 hours.
6. The material according to claim 3, characterized in that In S3, the reaction is carried out in solution; Preferably, the solvent is an ester organic solvent, preferably ethyl acetate; And / or, the temperature in S3 is 20-50° C., and the time is 1-4 hours.
7. The material according to claim 4, characterized in that The mass of montmorillonite in S4 is 1.5-2 times that of glycidyl ether modified with phenylphosphinic acid; and / or, S4 is mixed in water; Preferably, the water content in the mixture is ≤50wt%, preferably 10 to 50wt%; And / or, the temperature in S4 is 40° C.-100° C., and the time is 5-8 hours.
8. A method for preparing the polycarbonate (PC) / polyethylene terephthalate (PET) material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: SS1: melt-extrude and granulate PET, modified montmorillonite and optional processing aids to obtain PET masterbatch; SS2: After mixing PC and PET masterbatch, extrude and granulate them through a twin-screw extruder to obtain the target material.
9. The material according to claim 4, characterized in that In SS1, the temperature is 200-300°C and the screw speed is 200-800rpm; And / or, the temperature in SS2 is 200-300°C, and the screw speed is 200-800 rpm.
10. A use of a polycarbonate (PC) / polyethylene terephthalate (PET) material, wherein the material is the material according to any one of claims 1 to 7, or is prepared by the preparation method according to claim 8 or 9, and the material is used as a water-resistant polycarbonate (PC) / polyethylene terephthalate (PET) material, preferably in the field of new energy vehicles.
11. A montmorillonite modified with phenylphosphinic acid-modified glycidyl ether, wherein the montmorillonite is the montmorillonite used in the material according to any one of claims 1 to 7, or the montmorillonite used in the preparation method according to claim 8 or 9.
12. A method for preparing montmorillonite modified by phenylphosphinic acid-modified glycidyl ether, wherein the montmorillonite is the montmorillonite used in the material according to any one of claims 1 to 7, or the montmorillonite used in the preparation method according to claim 8 or 9, characterized in that: The modified montmorillonite is prepared by a method comprising the following steps: S1: phenylphosphinic acid is neutralized with an amine compound to obtain phenylphosphinic acid salt; S2: Eugenol reacts with epichlorohydrin to obtain eugenol glycidyl ether; S3: reacting eugenol glycidyl ether with phenylphosphinate to obtain phenylphosphinate-modified glycidyl ether; S4: mixing phenylphosphinic acid modified glycidyl ether with montmorillonite to obtain modified montmorillonite.
Citation Information
Patent Citations
Color-stable, Halogen-free Flame Retardant Compositions
CN102803368A
Antistatic anti-aging PC / PET (polycarbonate / polyethylene terephthalate) composite material and preparation method thereof
CN104672874A
Montmorillonite modifier
CN112794823A
Blending type barrier plastic packaging container
CN115536997A
Polymeric alloy material, preparation method therefor, and use thereof
WO2024066600A1